Project management performance and its influence on Malaysian building projects - Adeleke, A. Q.; Bamgbaded, J. A.; Salimon, Maruf Gbadebo; Lee, Chia Kuang (KnE Social Sciences, 2019)
Working environment and safety behavior are the primary concern in construction projects which in the long run are part of the yardstick in measuring project management performance. Construction safety and performance should be thoroughly investigated empirically by illustrating the current state of accident and performance in construction industries. Entrenched in the Malaysian construction industry experience, three dimensions of the project management performance (resolve cost, schedule, and quality) can buffer the contractor’s and project manager’s performance in building projects. Following organizational control theory, this research investigated the effects project management performance (resolve cost, schedule, and quality) on construction projects among G-7 contractors operating in Kuantan Malaysia construction industries through a personally administered questionnaire. Structural equation modeling (SEM) opined that schedule and quality have positive and significant influence, while resolve cost has a significant negative influence on Malaysia construction projects.